Modelling the production systems in industry 4.0 and their availability with high-level Petri nets. Issue 12 (2016) - Long, F.; Zeiler, P.; Bertsche, B.
Abstract: Industry 4.0 offers a new possibility to achieve a flexible and efficient production. Special features in industry 4.0 bring new challenges and have not been considered in the modelling yet. In this paper, extended coloured stochastic Petri nets (ECSPN) are used for modelling the production systems in industry 4.0 and their availability, in order to support the analysis and optimization of availability as well as of the supporting resources. Three models of ECSPN are built and simulated using a software REALIST to model interactions and self-organisation. Finally, the modelling results are explained.